Tingkat Konsentrasi Belajar Antara Santri Mondok dan Tidak Mondok: Studi Kasus di Pondok Pesantren al-Jauharen, Seberang Kota Jambi - Astuti Rahayu Ningsih (JIGC (Journal of Islamic Guidance and Counseling), 2021)
This study discusses the level of concentration between boarding and non-resident students at the Islamic boarding school al Jauharen. Located in the Al-jauharen Islamic boarding school across the city of Jambi, which is motivated by the level of concentration between boarding students and undocumented students, the researchers wanted to see from the difference in concentration levels between boarding and non-resident students at the Al-Jauharen Islamic boarding school across the city of Jambi. the number of students who lack concentration in studying at the pesantren. The purpose of this study was to find out how much the level of concentration in learning between boarding and non-resident students was at the MA level. The research method that the author uses is the descriptive quantitative method, and uses descriptive analysis techniques to see the level of learning concentration between boarding and non-student students. The subjects in this study amounted to 175 boarding students and 69 students who did not stay at the Al- Jauharen Islamic boarding school across the city of Jambi at the MA level. Based on the results of this study, it shows that: the level of concentration in the high category of boarding students is 19.01% (28 boarding students), the medium category is 69.4% (84 boarding students), and the low category is 11.6% (14 boarding students). ) based on this, it shows that the concentration of boarding students is in the medium category, namely 69.4%. the level of concentration of students who are not boarding students for the high category is 72.5% (29 students are not boarding), the medium category is 12.5% (5 students are not boarding), and the low category is 15% (6 students are not boarding) based on this shows that the concentration of students who do not stay in the high category is 72.5%. based on this, it shows that the students who do not stay are in the high category.